Play-Based Learning to Enhance Critical Thinking Capabilities - Bayu, Wahyu Indra; Maksum, Suroto; Ali (Faculty of Psychology, Universitas Surabaya, 2013)
The aim of this study was to test whether play-based learning with the focus on analysis, synthesis, and evaluation could enhance students’ critical-thinking capabilities. Subjects from two elementary schools were collected using cluster sampling (N = 61; with 27 receiving treatment and 34 not receiving treatment). In the pre-experiment the experiment group received treatment with the critical-thinking capabilities indicators being: (a) able to differentiate relevant and irrelevant information, (b productive in coming up with a solution, (c) able to deduct swiftly and accurately, (d) able to identify the truth of new information, and (e) able to ask complex questions. The results of the t-test showed a difference in the critical-thinking capabilities between the experiment group and the control group. It could be concluded that physical and health education through play-based learning using measurable principles could enhance students’ critical-thinking capabilities. Penelitian ini menguji apakah pembelajaran melalui aktivitas bermain yang menekankan analisis, sintesis, dan evaluasi, mampu meningkatkan kemampuan berpikir kritis siswa. Dengan cluster sampling diperoleh subjek dari dua sekolah dasar (N = 61; 27 dikenai perlakuan dan 34 tanpa perlakuan). Melalui eksperimen semu diberikan perlakuan terhadap kelompok eksperimen yang indikator kemampuan berpikir kritisnya adalah: a) mampu membedakan informasi yang relevan dan tidak relevan, (b) produktif dalam memberikan solusi, (c) mampu menyimpulkan dengan cepat dan tepat, (d) mampu mengidentifikasi kebenaran informasi baru, dan (e) mampu bertanya hal-hal kompleks. Hasil t-test menunjukkan ada perbedaan kemampuan berpikir kritis antara kelompok ekperimen dan kelompok kontrol. Dapat disimpulkan bahwa pembelajaran pendidikan jasmani, olahraga, dan kesehatan melalui aktivitas bermain yang berdasarkan kaidah-kaidah terukur mampu melatih anak meningkatkan kemampuan berpikir kritisnya.